FOREWORD FROM HANDLING EDITOR - 4TH EDITION - Sodri, Ahyahudin (Journal of Environmental Science and Sustainable Development, 2020)
We are delighted to present the 4th edition of JESSD, published in July 2020. We have selected ten of the best articles for this edition from Environmental Science and Sustainable Development topic.